2019
DOI: 10.9770/jssi.2019.8.3(14)
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Corporate Social Responsibility Applied to the Concept of Sustainable Development

Abstract: This article is a continuation of the historical overview of corporate social responsibility (CSR), took place in the 20th century. The main definitions, principles, actions were explained with the purpose of research the influence if the kinds of responsibilities as legal, ethical, philanthropic on the sustainable development of the enterprise. The consequent CSR concepts observations are presented, namely Social Responsibility of Business Man, Stakeholder Approach, Three dimensional model, Three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A study conducted by the authors revealed that more attention should be paid to increasing the value of CSR and creating favorable conditions for businesses to invest socially. Most effectively, these tasks can be solved taking into account three principles, such as ensuring CSR voluntariness, development of CSR within the framework of sustainable development [18] and taking into account regional features. Companies can also contribute to the development of the CSR institute by combining their projects into a comprehensive CSR practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by the authors revealed that more attention should be paid to increasing the value of CSR and creating favorable conditions for businesses to invest socially. Most effectively, these tasks can be solved taking into account three principles, such as ensuring CSR voluntariness, development of CSR within the framework of sustainable development [18] and taking into account regional features. Companies can also contribute to the development of the CSR institute by combining their projects into a comprehensive CSR practice.…”
Section: Resultsmentioning
confidence: 99%
“…According to an international survey of 30,000 people conducted by Neilsen in 60 countries in 2014, on average 55% of consumers are willing to pay more for products and services provided by socially responsible companies 18 . And this share increases.…”
Section: Recommendations For Other Actorsmentioning
confidence: 99%
“…CSR is the practice by which a business, no matter its size or number of employees, views itself as a member of society with certain implicit social obligations regarding environmental considerations and issues [13]. Several scholars have offered some classifications of the concept based on the chronological development of CSR and have summarized the evolution of cooperation phenomena between businesses [14].…”
Section: Corporate Social Responsibility (Csr): Principles and Modelsmentioning
confidence: 99%
“…Yevdokimova [14] shares and reinforces the CSR concept from the viewpoint of four categories of cooperation phenomena between business and society developed by Garriga and Mele [15]. The first category includes instrumental theories, whereby economic goals are achieved through social activities assuming that enterprises are instruments for wealth creation.…”
Section: Corporate Social Responsibility (Csr): Principles and Modelsmentioning
confidence: 99%
“…Moreover, it is required that the sustainable development strategy would be correlated with the entity's activities and be capable to adapt to the constantly changing environment [2]. This is possible only if the entity's approach is responsible and takes into account the potential risks that may influence its strategy [9].…”
Section: Introductionmentioning
confidence: 99%